Broccoli seed sprouts as a functional ingredient in gluten-free cake based on rice flour - Maniya Mohammadi; Fariborz Nahidi; Marzieh Bolandi (Applied Food Research, 2025)
Functional products rich in dietary fiber, antioxidants, and polyunsaturated fatty acids, significantly impact consumer health. This research aims to enhance gluten-free cake using broccoli sprout powder (BSP) in rice flour. Different levels of BSP (0, 5, 10, 15 and 20%) were added to rice flour, and the rheological behavior, chemical composition, pH, water activity, specific volume, porosity, antioxidant activity, texture parameters, color indices, fatty acid profile, and sensory characteristics of the gluten-free cake were examined. The study found that increasing BSP level increased cake content in moisture, total ash, protein, fat, and fiber, but decreased its pH (p < 0.05). BSP-enriched cakes exhibited higher specific volume, porosity, and a softer texture. As BSP level increased, crust and crumb L* index decreased, while a*, b*, and ΔE indices increased. BSP also demonstrated remarkable antioxidant activity, with enriched cakes showing a significant increase in antioxidant activity (p < 0.05). BSP-enriched cakes have higher polyunsaturated fatty acid content, higher sensory acceptance, and higher sensory scores than the control sample, indicating functional gluten-free (GF) cakes with antioxidant compounds and dietary fiber.